Impact of Spatial Effect on Volatility of Trade - Zarra-Nezhad, Mansour; Mansouri, Amin (Asian Journal of Empirical Research, 2014)
The main objective of this study is to evaluate the spatial volatility of trade based on the Spatial Panel data Econometric Method and Wavelet Smoothing. The negative spatial dependents are estimated. So that, an increase by one percent in trade volatility and unknown volatility in neighboring countries causes 2.1, 0.55 percent increase in trade volatility of each country in the reverse direction, respectively. Evaluation of results of spillover elasticity of trade volatility suggests that volatility in the prices, growth rate and GDP in neighboring countries causes an increase in trade volatility in the opposite direction and other variables increase in the same direction. Based on these results, the growth rate volatility in the opposite direction and geographical concentration in the same direction plays the greatest impact in the trade volatility. Therefore, the estimation results of OLS without spatial effects are biased.